(NkITAJSKIJ \TNOS NA POROGE SREDNIH WEKOW (B/s - (NkR@KOW(B, (NmIHAIL wASILXEWI^s; (NsOFRONOW(B, (NmIHAIL wIKTOROWI^s; (NiNSTITUT dALXNEGO wOSTOKA an sssrs; (NiNSTITUT \TNOGRAFII IM(B. (Nn(B.(Nn(B. (NmIKLUHO(B-(NmAKLAQ an sssrs ((NmOSKWA (B:s (NnAUKA(B,s, 1979)
(NrEZ(B. (NNA ANGL(B. (NQZ(B.: (NS(B. 322-324s
(NbIBLIOGR(B.: (NS(B. 284-303s
Keywords: (NkITAJSKAQ KULXTURAs -- (NiSTORIQs -- 3-6 (NWW(B.s; (NkITAJCY s -- (N|TNOGENEZs